Did the Revision of the ECB Monetary Policy Strategy Affect the Reaction Function? - Roberta Colavecchio; Kai Carstensen (Kiel Institute for World Economics (IfW), 2004)
In May 2003 the European Central Bank (ECB) announced the revision of its monetary policy strategy. Although the ECB stressed that the revision would not imply any fundamental change in their decisions, this remains to be verified empirically. Therefore, this paper tries to answer the question whether the strategy revision has induced a structural break in the ECB policy reaction function. To this end, we estimate several Taylor-type reaction functions and conduct a structural change analysis using both recursive parameter estimates and structural change tests. We find that the ECB has been following a stabilizing rule and that there is no clear-cut evidence in favor of a break after the revision, even though some signals of instability show up, particularly in June 2003.
Keywords: 330; Geldpolitik; Schätzung; Strukturbruch; Europäische Wirtschafts- und Währungsunion; EU-Staaten; Reaktionsfunktion